Identification and biological examination of some inland Monilinia species - Fazekas, Mónika; Szalóki, Szilvia; Madar, Anett; Miklós, Ida; Holb, Imre (Acta Agraria Debreceniensis, 2012)
The aim of this study was to identify and biologically analyse some Monilinia species from Hungary. 146 M. fructigena and 28 M. laxa species out 174 infectious fruit from all over the country were used for the study. For further study 10 isolates were used and apple fruit was inoculated with them according to Koch postulate. 1–2 mm ochre exogen stromas were observbed on infectious plant parts and growing signs on culture of all isolates were identical to M. fructigena. To affirm classical identification, isolates with molecular biological method were also prepared using PCR reaction. Control isolates of M. laxa, M. fructigena and M. fructicola were used. The size of PCR product showed that all isolates had a 415 bp band which was typical of  M. fructigena. Results support the previous observation that M. fructigena and M. laxa species occure all over Hungary.